Editorial - Edgar Lucero (HOW, 2019)
Autonomy has been of interest to scholars in the Colombian field of English language education over the last two decades. A constant work on understanding what it is, how to foster it in local language students by varied alternatives, or to examine it in homegrown language teachers has been paramount in published research reports and articles of reflection in Colombia. Different possibilities are at hand, possibilities that account for contextual factors as well as local teachers’ and students’ backgrounds and variables.